Carbon-doped CuFe2O4 with C--O--M channels for enhanced Fenton-like degradation of tetracycline hydrochloride: From construction to mechanism - Hong Qin; Yangzhuo He; Piao Xu; Yuan Zhu; Han Wang; Ziwei Wang; Yin Zhao; Haijiao Xie; Quyang Tian; Changlin Wang; Ying Zeng; Yicheng Li (Green Energy & Environment, 2024)
Carbon-doped copper ferrite (C–CuFe2O4) was synthesized by a simple two-step hydrothermal method, which showed enhanced tetracycline hydrochloride (TCH) removal efficiency as compared to the pure CuFe2O4 in Fenton-like reaction. A removal efficiency of 94% was achieved with 0.2 g L−1 catalyst and 20 mmol L−1 H2O2 within 90 min. We demonstrated that 5% C–CuFe2O4 catalyst in the presence of H2O2 was significantly efficient for TCH degradation under the near-neutral pH (5–9) without buffer. Multiple techniques, including SEM, TEM, XRD, FTIR, Raman, XPS Mössbauer and so on, were conducted to investigate the structures, morphologies and electronic properties of as-prepared samples. The introduction of carbon can effectively accelerate electron transfer by cooperating with Cu and Fe to activate H2O2 to generate ·OH and ·O2−. Particularly, theoretical calculations display that the p, p, d orbital hybridization of C, O, Cu and Fe can form C–O–Cu and C–O–Fe bonds, and the electrons on carbon can transfer to metal Cu and Fe along the C–O–Fe and C–O–Cu channels, thus forming electron-rich reactive centers around Fe and Cu. This work provides lightful reference for the modification of spinel ferrites in Fenton-like application.